The Effect of the Genre-Based Approach on Academic Writing Skills - Mega Riyawati; Siti Mariyah; Muhammad Nur (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to evaluate the effectiveness of the Genre-Based Approach (GBA) in improving the academic writing skills of sixth-semester PGMI students at IAI Miftahul Ulum Tanjungpinang. The research employed a pre-experimental design with a one group pretest-posttest pattern, involving 32 students as participants. Data were collected through written tests (pretest and posttest), classroom observations, questionnaires, and in-depth interviews. Quantitative data were analyzed using the Wilcoxon Sign-Rank Test with the assistance of SPSS, while qualitative data were analyzed thematically. The results show a significant improvement in students’ academic writing scores after the implementation of GBA, with the average score increasing from 66.88 (pretest) to 81.34 (posttest). The Wilcoxon Sign-Rank Test yielded an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a statistically significant difference between students’ writing abilities before and after the intervention. Additionally, students demonstrated better understanding of academic text structure, increased motivation, and more frequent, use of valid references. However, some students still experienced difficulties in constructing logical arguments and initiating the writing process. These findings confirm that the Genre-Based Approach is effective in enhancing academic writing skills among PGMI students and can serve as a reference for developing writing instruction strategies in higher education